Changes in pronoun use a decade before clinical diagnosis of Alzheimer’s dementia: linguistic contexts suggest problems in perspective-taking - Bittner, Dagmar; Frankenberg, Claudia; Schröder, Johannes (Brain Sciences, 2022)
The use of pronouns has been shown to change pathologically in the early phases of Alzheimer’s Dementia (AD). So far, the findings have been of a quantitative nature. Little is known, however, about the developmental path of the change, its onset, the domains in which it initially occurs, and if and how it spreads to other linguistic domains. The present study investigates pronoun use in six speakers of German a decade before they were clinically diagnosed with AD (LAD) and six biographically matched healthy controls (CTR). The data originate from monologic spoken language elicited by semi-spontaneous biographical interviews. Investigation of nine pronoun types revealed group differences in the use of three pronoun types: D-pronouns—a specific pronoun type of German for reference to persons and objects; the impersonal pronoun man ‘one’, and the propositional pronoun das ‘this/that’. Investigation of the linguistic contexts in which these three pronoun types were used revealed a correlation with declines in elaborative and evaluative information; that is, information the hearer would benefit from in creating an informed model of the discourse. We, therefore, hypothesize that the early changes in language use due to AD point to problems in perspective-taking, specifically in taking the hearer’s perspective.
Gesehen am 08.09.2022